2020
DOI: 10.1063/5.0012330
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence on bandgap of semiconductor photocatalysts

Abstract: Light irradiation onto a semiconductor generates heat; however, its electronic structure under high temperature has not yet been well investigated. In this study, we have carefully examined the temperature dependence on the bandgap of simple metal oxides, which are well-known photocatalysts, i.e., TiO2, CeO2, Nb2O5, SnO2 Ta2O5, WO3, ZnO, and ZrO2, using operando UV–visible spectroscopy under controlled temperature (from room temperature to 500 °C). Consequently, a linear decrease in bandgap was seen as a funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Pan et al [46] and Han et al [51] also found that photocatalytic activity increased as they induced heat energy (Figure 56). Very recently, we found that the absorption spectra of semiconductors are largely changed under heat treatment, which was analyzed by operando UV-vis spectroscopy [73]. This bandgap shift phenomenon should be considered since the surface temperature of most of the photocatalysts increases, especially for gas-phase reactions, such as methane conversion.…”
Section: Bandgap Shift Due To Thermal Energymentioning
confidence: 99%
See 3 more Smart Citations
“…Pan et al [46] and Han et al [51] also found that photocatalytic activity increased as they induced heat energy (Figure 56). Very recently, we found that the absorption spectra of semiconductors are largely changed under heat treatment, which was analyzed by operando UV-vis spectroscopy [73]. This bandgap shift phenomenon should be considered since the surface temperature of most of the photocatalysts increases, especially for gas-phase reactions, such as methane conversion.…”
Section: Bandgap Shift Due To Thermal Energymentioning
confidence: 99%
“…Therefore, an evaluation of the absorption spectra under heat input (operando UV-vis absorption spectra) is very important for determining the photocatalytic performance factors, such as internal quantum efficiency. Very recently, we found that the absorption spectra of semiconductors are largely changed under heat treatment, which was analyzed by operando UV-vis spectroscopy [73]. This bandgap shift phenomenon should be considered since the surface temperature of most of the photocatalysts increases, especially for gas-phase reactions, such as methane conversion.…”
Section: Figure 55mentioning
confidence: 99%
See 2 more Smart Citations
“…We speculate this slight response under the cutoff filter would depend on the intrinsic electric structural change in the YSZ at high temperatures. Thus, we measured the optical absorption spectrum of the YSZ powder at the controlled temperature conditions using an Operando UV‐Vis spectroscope [45] equipped with a heat chamber as shown in Supporting Information (Figure S10). As a result, bandgap narrowing of the YSZ was seen under high temperatures.…”
Section: Resultsmentioning
confidence: 99%